Capacitance-voltage and Auger chemical profile studies on AlGaN/GaN structures passivated by SiO2/Si3N4 and SiNx/Si3N4 bilayers - Adamowicz, Bogusława; Miczek, Marcin; Hashizume, Tamotsu; Klimasek, Andrzej; Bobek, Piotr; Żywicki, Janusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
AlGaN/GaN heterostructures passivated by SiO2/Si3N4 and SiNx/Si3N4 bilayers were characterized electrically by capacitance-voltage measurements and chemically by Auger microscopy chemical in-depth profiling. The 2-dimensional electron gas density was estimated from C-V curves and the electronic quality of the bilayers was evaluated from C-V hysteresis. Detailed variations of Auger peaks, in particular for oxygen, silicon, nitrogen, and carbon, versus argon ion sputtering time were registered. The electronic properties of these two structures were compared with each other and to their chemistry.
Optica Applicata, Vol. 37, 2007, nr 4, s. 327-334
Keywords: optyka; gallium nitride; HEMT; insulated gate; passivation; C-V; Auger spectroscopy; chemical in-depth profiles